Bulk substrate porosity verification by applying Monte Carlo modeling and Castaing’s formula using energy-dispersive x-rays - Yung, L.C.; Fei, C.C.; Mandeep, J.S.; Amin, N.; Lai, K.W. (International Society for Optical Engineering (SPIE), 2015)
The leadframe fabrication process normally involves additional thin-metal layer plating on the bulk copper substrate surface for wire bonding purposes. Silver, tin, and copper flakes are commonly adopted as plating materials. It is critical to assess the density of the plated metal layer, and in particular to look for porosity or voids underneath the layer, which may reduce the reliability during high-temperature stress. A fast, reliable inspection technique is needed to assess the porosity or void weakness. To this end, the characteristics of x-rays generated from bulk samples were examined using an energy-dispersive x-ray (EDX) detector to examine the porosity percentage. Monte Carlo modeling was integrated with Castaing's formula to verify the integrity of the experimental data. Samples with different porosity percentages were considered to test the correlation between the intensity of the collected x-ray signal and the material density. To further verify the integrity of the model, conventional cross-sectional samples were also taken to observe the porosity percentage using Image J software measurement. A breakthrough in bulk substrate assessment was achieved by applying EDX for the first time to nonelemental analysis. The experimental data showed that the EDX features were not only useful for elemental analysis, but also applicable to thin-film metal layer thickness measurement and bulk material density determination. A detailed experiment was conducted using EDX to assess the plating metal layer and bulk material porosity.